Opioid Inhibition of Hippocampal Interneurons via Modulation of Potassium and Hyperpolarization-Activated Cation (I(h)) Currents - Svoboda, Kurt R. (J Neurosci, 1998)
The actions of mu- and delta-opioid agonists (DAMGO and DPDPE, respectively) on GABAergic interneurons in stratum oriens of area CA1 of the hippocampus were examined by using whole-cell voltage-clamp recordings in brain slices. Both agonists consistently generated outward currents of similar magnitude (15–20 pA) in the majority of cells. However, under control conditions, current–voltage (I/V) relationships revealed that only a small number of these cells (3 of 77) demonstrated clear increases in membrane conductance, associated with the activation of the potassium current known as G(irk). These interneurons also exhibited a slowly activating, inwardly rectifying current known as I(h) on hyperpolarizing step commands.I(h) was blocked by the extracellular application of cesium (3–9 mm) or ZD 7288 (10–100 μm) but was insensitive to barium (1–2 mm). In an effort to determine whether the holding current changes were attributable to the modulation of G(irk)and/or I(h), we used known blockers of these ion channels (barium or cesium and ZD 7288, respectively). Extracellular application of cesium (3–9 mm) or ZD 7288 (25–100 μm) blocked I(h) and significantly reduced the opioid-induced outward currents by 58%. Under these conditions the opioid agonists activated a potassium current with characteristics similar toG(irk). Similarly, during barium (1–2 mm) application the opioid-induced outward currents were reduced by 46%, and a clear reduction in I(h)and the whole-cell conductance was revealed. These data suggest that the opioids can modulate both I(h) andG(irk) in the same population of stratum oriens interneurons and that the modulation of these ion channels can contribute to the inhibition of interneuron activity in the hippocampus.